The Impact of Internal Auditor Compensation and Role on External Auditors' Planning Judgments and Decisions - DEZOORT, F. TODD; HOUSTON, RICHARD W.; PETERS, MICHAEL F. (Contemporary Accounting Research, 2001)
This paper reports the results of an experiment that investigates how external audit planning is affected when internal auditors have incentives and the opportunity to bias their evaluations. Specifically, we draw on attribution theory to examine how internal auditor eligibility for incentive compensation and participation in consulting (i.e., two factors that provide incentives to bias audit evaluations) affect external audit planning. In addition, we examine the effects of incentive compensation and a consulting role across two routine internal audit tasks — an objective tests of controls task and a subjective inventory valuation task — to evaluate whether their effects are contingent upon task subjectivity (i.e., opportunity to bias audit evaluations). Seventy-six external auditors from four Big 5 public accounting firms participated in an experiment that manipulated internal auditor compensation (fixed salary versus incentive compensation), the type of work that the internal auditors routinely perform (primarily auditing versus primarily consulting), and audit task subjectivity (objective tests of controls versus subjective inventory valuation). Our results suggest that the nature of internal auditors' compensation and work affect audit planning recommendations differently. The opportunity to receive incentive compensation results in less reliance on internal auditors' work and greater budgeted audit hours, but only for the subjective task. Although a consulting role decreases perceived internal auditor objectivity, it has a limited effect on planning recommendations. Specifically, consulting has no effect on reliance, and leads to greater budgeted audit hours only when incentive compensation is available. We discuss potential explanations for the results as well as implications for audit research, practice, and regulation.